EgMIXTA1, a MYB-Type Transcription Factor, Promotes Cuticular Wax Formation in Eustoma grandiflorum Leaves - Wang, Lishan; Xue, Wanjie; Li, Xueqi; Li, Jingyao; Wu, Jiayan; Xie, Linan; Kawabata, Saneyuki; Li, Yuhua; Zhang, Yang (Frontiers in Plant Science, 2020)
Cuticular wax forms a hydrophobic layer on plant aerial organs that can protect cells from dehydration, repel pathogen attack, and prevent organ fusion during development. The MIXTA gene encodes an MYB-like transcription factor and associates with epicuticular wax biosynthesis to increase leaf surface wax load. Here, we functionally characterized the AmMIXTA-homologous gene EgMIXTA1 in Eustoma grandiflorum. EgMIXTA1 was ubiquitously expressed but most highly expressed in leaves and buds. Compared with the wild type, EgMIXTA1-overexpressing plants had more wax crystal deposition on the leaf surface and significantly more total cuticular wax. Cuticular transpiration occurred more slowly in the leaves of overexpression lines than in those of non-transgenic plants. Gene expression analysis indicated that a number of genes, such as EgCER3, EgCER6, EgCER10, EgKCS1, EgKCR1and EgCYP77A4, which are known to be involved in wax biosynthesis, were induced in EgMIXTA1 overexpressors. The expression of another gene, WAX INDUCER1/SHINE1, encoding a transcription factor that promotes cutin production, was also significantly higher in the overexpressors than in wild type. However, the expression of a gene related to lipid transport, EgABCG12, did not change compared with wild type. Taken together, our results suggest that EgMIXTA1 is involved in cuticular wax biosynthesis.